Blended psychotherapy: integrated intervention - Iannazzo, Antonio; Stefano, Stefano; Ruggero, Luana Zaira; Santonicola, Caterina; Armenante, Olimpia; Motta, Vincenzo; Degano, Anna; Rosa, Veronica (Phenomena Journal - International Journal of Psychopathology, Neuroscience and Psychotherapy, 2023)
This article constitutes the first part of an in-depth work on blended therapeutic intervention on trauma. The objective is starting from the various meanings of the terms blended, online, presence, describing their genesis and evolution, to delve into the possibilities that presence/distance integration can offer to the treatment of trauma. This first article will more focus on the meanings of the term blended, as the possibility of building an intervention through the use of various tools, which can be video chats, e-mails, text chats, the telephone, presence, the metaverse. Furthermore, some international experiences and some tools/platforms/software for remote working will be reported. An in-depth analysis of the term trauma and how to use it for trauma intervention will be explored in depth in the second article (in press).